Customers Percepions and Their Choices of Fuel Stations in Uganda. Acase Study of Jinja Iganga Highway - Rebecca Nanjiya (Uganda Christian University, 2025)
The objective of the research was to investigate how consumers' perceptions interact with the fuel stations they attend on Uganda's Jinja-Iganga highway. Using a mixed-methods study to both collect quantitative and qualitative data, this research investigates the impact of perceived service quality, price, and location on consumers' decisions. The findings support the premise that all three variables service quality, price, and location are important in influencing consumer choice. The customers value courtesy and politeness of service, reasonable speed of service, and highly knowledgeable staff, all of which contribute to creating a positive perception of quality. Price is significant, and many consumers are ready to go to another station due to low price, though they also value reasonable and competitive pricing. In addition, accessible location, easy accessibility, and pleasant physical appearance were all found to be significant in order to attract and retain customers. The study determines that gas stations along this highway must strategically focus on these three variables in a bid to acquire and maintain competitive advantage. The managers are advised to prioritize employees' training, adopt competitive prices policy, and optimize the physical configuration of their stations, the report says. It is suggested that future studies can broaden the geographical coverage and consider other variables including brand loyalty schemes and non-fuel services' impact.
Undergraduate thesis